Sistem Budaya Pendidikan Di Madrasah - Muhammad Satir (Al-Riwayah : Jurnal Kependidikan, 2020)
This paper examines the cultural system of education in Madrasah Tsanawiyah Negeri (MTsN) Model City of Sorong. Madrasah education culture is something that is built from the findings of the meeting between the values ​​adopted by the head of the madrasah as a leader and the values ​​shared by teachers and employees at the madrasah. The Madrasah educational cultural system plays an important role in increasing human resources to become humans who have knowledge, skills and noble morals. It is hoped that the existence of a madrasa education culture will emerge a generation that will benefit the environment. If the cultural environment of madrasah education is clean, the filler of the existing culture in the madrasah, both teachers, students, parents, and others will feel comfortable. Conversely, if the environment is not well maintained, the madrasa community will feel uncomfortable and ultimately will not feel happiness. The results of this study are: First, the educational culture system in madrasah is the result of a combination of the values ​​held by the head of the madrasah as a leader with the values ​​shared by teachers, administrative staff, library employees or all employees at the madrasah. the. The meeting of these ideas then results in an organization, then a form of shared values ​​appears and these values ​​become the main burden of cultural formation in madrasas. From this culture, visible symbols and actions emerged that could be observed and felt in life in madrasas. Second, the activities carried out by the Sorong City Model MTsN which have become a culture in the Madrasah environment are as follows; congregational prayer at the MTsN Model mushallah, reading the holy verses of the Al-Qur`an every morning before teaching and learning activities, holding qurban every year from students and teachers, conducting art performance competitions, PMR (Youth Red Cross) extracurricular activities and Scouts, raising social funds from both teachers and students, and class cash.